2011
DOI: 10.1111/j.1540-8183.2011.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Fraction Flow Reserve to Predict Changes over Time in Management of Superficial Femoral Artery

Abstract: This is the first study to demonstrate that the peripheral vascular bed does respond to vasodilatation thereby supporting the use of pFFR for this procedure. In our study, postintervention pFFR < 0.95 predicted a more rapid increase in PSV over time, which is a reasonably accepted surrogate for restenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 30 publications
0
22
0
Order By: Relevance
“… 3 , 4 Various parameters have been proposed to determine hemodynamic significance, including mean pressure gradient (MPG), peak-to-peak PG, and ratio of mean pressure (also referred to as the peripheral fractional flow reserve [pFFR]) with or without vasodilators. 5 9 However, the validity of these parameters for treatment planning is unclear. Therefore, the purpose of this study was to verify whether trans-stenotic absolute PG and pFFR measured using a 0.014-inch pressure wire under hyperemia can be used to establish hemodynamic significance in iliofemoral angiographically intermediate stenosis.…”
Section: Introductionmentioning
confidence: 99%
“… 3 , 4 Various parameters have been proposed to determine hemodynamic significance, including mean pressure gradient (MPG), peak-to-peak PG, and ratio of mean pressure (also referred to as the peripheral fractional flow reserve [pFFR]) with or without vasodilators. 5 9 However, the validity of these parameters for treatment planning is unclear. Therefore, the purpose of this study was to verify whether trans-stenotic absolute PG and pFFR measured using a 0.014-inch pressure wire under hyperemia can be used to establish hemodynamic significance in iliofemoral angiographically intermediate stenosis.…”
Section: Introductionmentioning
confidence: 99%
“…39 In patients with claudication, initial studies have shown that FFR measurements correlate with the lesion peak systolic velocity, a noninvasive measurement of lesion severity. 40 Further studies will be necessary to correlate the clinical use of FFR measurements to potentially guide revascularization or other treatment strategies in PAD.…”
Section: Exercise Hemodynamicsmentioning
confidence: 99%
“…3 A). Fractional flow reserve (FFR), which measures the pressure gradient across stenotic arteries, was increased in arteries with larger cross-sectional lumen areas 16 , 17 . The FFR value in the SDT group (Fig.…”
Section: Resultsmentioning
confidence: 99%